ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL-SOAL CERITA DI UPTD SMP NEGERI 5 KUPANG - Anu, Elisabet; Ralmugiz, Uke; Aba, Maria Martini (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2024)
This study aims to determine the ability of students' mathematical connections in solving story problems. The research used was qualitative research, with the research subject of class VIII B students of UPTD SMP Negeri 5 Kupang. The research instruments used are tests, interviews and documentation. The data that has been obtained is then analyzed using question instrument analysis, data classification, and conclusions. The results showed that 3 students with high mathematical connection skills with a value of 12% were able to master all three indicators, namely linking concepts and procedures in mathematics, linking concepts in mathematics with other sciences, and applying mathematical concepts to everyday life. 11 Students with moderate mathematical connections with a score of 44% only mastered a few indicators, namely relating concepts in mathematics to other sciences, and applying mathematical concepts to everyday life.